Process and Techno-economic Analysis of Bio-jet Fuel-range Hydrocarbon Production from Lignocellulosic Biomass Via Aqueous Phase Deconstruction and Catalytic Conversion. (May 2017) - Li, Yuping; Chen, Lungang; Zhang, Xinghua; Zhang, Qi; Wang, Tiejun; Qiu, Songbai; Tan, Jin; Li, Kai; Ma, Longlong
Abstract: The integrated 1000 tonne/a-scale bio-jet fuel-range hydrocarbon (C8 -C15 ) synthesis system via aqueous phase deconstruction and catalytic conversion process was analyzed for its techno-economics of biomass residue utilization. The operation characterization, mass flow and cost in the system were discussed. A two-step deconstruction of corncob, steam stripping and acidic hydrolysis, was designed for the production of the platform chemicals, furfural and levulinic acid from hemicellulose and cellulose respectively. The oxygenate intermediates with the increased carbon chain length was produced by alkali catalyzed aldol condensation from furfural and levulinic acid. The oxygenate intermediates were catalytically converted to jet fuel-range hydrocarbon (C8 -C15 ) by the tandem steps of low-temperature hydrogenation, high-temperature hydrodeoxygenation and upgrading over noble metal catalysts. The results indicated that bio-jet fuel yield is 139 kg/h or 8 tonne of dried corncob for 1 tonne fuel production. The operation cost of bio-jet fuel is about $1540/tonne and the cost on corncob, catalytic catalyst and H2 contributed 23%, 19% and 16% respectively. The cost sensitivity analysis showed that the catalytic lifetime was one of the main factors that affected the economics of bio-jet fuel production, which could increase bio-jet fuel price to $1820/tonne when its lifetime was reduced to 0.5 year.